Desafios da intersetorialidade entre trabalho e saúde mental - Sayeg, Evelyn (2017)
In order to discuss the intersectorial construction of Public Policies based on its historical and social construction, this master's thesis was based on analyzing the challenges and possible arrangements in the construction of the Mental Health and Work and Income Policies articulation as a project of achievement of the participation of users of mental health services in the social body. For this, we sought to analyze the experience of a work center belonging to the Network of Psychosocial Care of a municipality, in this case the Center of Work and Art of São Bernardo do Campo. The transformations about the Capital – Labor relationship act in the direction of an extension of the phenomenon of social inequality. At the same time it seeks to transform the understanding of society about the phenomenon of madness, understanding that this is part of the human condition and therefore, there is no way to eliminate the madness of society. However, it poses as a possibility of expanding the spaces of participation in the social body to the “crazy people”, while, it was possible to find more just, dignified and solidary work possibilities, based on the guidelines of the Solidary Economy. The challenges and shared care proposals that the analysis, found in the dissertation, point to processes of intersectoriality and transversalization of care. Breaking with the resistances that present themselves in the daily work process of the health services, fit and become part of the process of construction of the singular therapeutic project, the work ruling contributes to the expansion of the service's view, as well as its care practice . Making possible directions that talk about the limitation of the place of health in the conduction of the encounter with the citizenship and the power to expand the guidelines of the Anti Asylum Psychiatric Reform to new areas of the society